Ende natural zeolite as a catalyst in the biodiesel production from nyamplung oil - Gregorio Antonny Bani; Mario Donald Bani (Institute of Computer Science (IOCS), 2023)
Fuel use as a primary energy source is increasing daily, and the reserves of these natural resources are diminishing quickly. Different studies have been performed to see the potential use of the seeds of the Nyamplung plant (Chalophyllum inophyllum L.) as biodiesel. To produce biodiesel from Nyamplung oil, a catalyst, such as zeolite, is often required to speed up the reaction, save energy use, and increase the quantity and quality of the biodiesel. There is a high variation in terms of natural zeolite’s catalytic activity, depending on the location where the zeolite was formed in the past. The objectives of this study were to characterize and understand the Ende natural zeolite, before and after activation, and to see the catalytic activity of the HCl-activated zeolite in the production of biodiesel from Nyamplung oil. When zeolite was used as a catalyst, optimum effects on the esterification were observed at 700 rpm stirring speed with a reaction time of 15 minutes. These conditions optimally converted 100% of Nyemplung oil into biodiesel.